2022
DOI: 10.1002/adhm.202101737
|View full text |Cite
|
Sign up to set email alerts
|

2D Covalent Organic Framework Direct Osteogenic Differentiation of Stem Cells

Abstract: 2D covalent organic frameworks (COFs) are an emerging class of crystalline porous organic polymers with a wide-range of potential applications. However, poor processability, aqueous instability, and low water dispersibility greatly limit their practical biomedical implementation. Herein, a new class of hydrolytically stable 2D COFs for sustained delivery of drugs to direct stem cell fate is reported. Specifically, a boronate-based COF (COF-5) is stabilized using amphiphilic polymer Pluronic F127 (PLU) to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Nanoparticles (NPs) such as liposomes, polymeric NPs, inorganic NPs, etc., are being used as drug carriers for decades [ 80 , 81 , 82 , 83 , 84 , 85 ]. Drug loading in NPs enhances circulation life of hydrophobic drugs in blood, protect nucleic-acid-based therapeutics from serum nucleases, or reduce the adverse off-target effects of drugs [ 86 , 87 , 88 , 89 , 90 ]. Surface of NPs can be engineered with PEG to achieve longer circulation life or with cell-penetrating peptide to enhance cellular uptake [ 91 ], or with targeting ligand to selectively deliver the payloads at targeted tissue [ 92 ].…”
Section: Approaches For Drug Delivery Through the Blood–brain Barriermentioning
confidence: 99%
“…Nanoparticles (NPs) such as liposomes, polymeric NPs, inorganic NPs, etc., are being used as drug carriers for decades [ 80 , 81 , 82 , 83 , 84 , 85 ]. Drug loading in NPs enhances circulation life of hydrophobic drugs in blood, protect nucleic-acid-based therapeutics from serum nucleases, or reduce the adverse off-target effects of drugs [ 86 , 87 , 88 , 89 , 90 ]. Surface of NPs can be engineered with PEG to achieve longer circulation life or with cell-penetrating peptide to enhance cellular uptake [ 91 ], or with targeting ligand to selectively deliver the payloads at targeted tissue [ 92 ].…”
Section: Approaches For Drug Delivery Through the Blood–brain Barriermentioning
confidence: 99%
“…Bhunia et al also reported new 2D COF–polymer nanoparticles for drug delivery by combining colloidal COF-5 and an amphiphilic polymer, which was the first report demonstrating the osteoinductive ability of COFs. 218 They not only found that the 2D COF was able to induce osteogenic differentiation of hMSCs in the absence of an osteoinductive agent, but also loaded the osteoinducing agent dexamethasone within the porous structure of COFs to further enhance the osteoinductive ability, demonstrating the impressive features and great potential of COFs for wider applications.…”
Section: Bio-related Applications Of Cofsmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are emerging crystalline porous organic polymers for the sustained delivery of drugs [ 22 ]. For example, Bhunia et al fabricated a boronate-based COF loaded with dexamethasone and demonstrated that the hydrolytically stable COF nanocomposite was able to induce MSC osteogenic differentiation in the absence of an osteoinductive agent [ 23 ]. Hydrogels are widely applied in bone tissue engineering for cell adhesion and drug delivery due to their controllable mechanical properties, superior biocompatibility, and excellent drug loading capacity [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%